Genetic mapping of the FACC gene and linkage analysis in Fanconi anaemia families. Issue 11 (November 1994) - Gibson, R A; Ford, D; Jansen, S; Savoia, A; Havenga, C; Milner, R D; de Ravel, T J; Cohn, R J; Ball, S E; Roberts, I
Abstract : Fanconi anaemia is an autosomal recessive disorder associated with increased chromosome breakage and progressive bone marrow failure. The gene for complementation group C (FACC) has been cloned and mapped to chromosome 9q22.3, but neither its genetic location nor the proportion of patients belonging to group C is known. We have used a polymorphism within the FACC gene to localise it within a 5 cM interval on chromosome 9q, bounded by D9S196/D9S197 and D9S176. The genes for Gorlin's syndrome and multiple self-healing squamous epitheliomata have also been mapped to this interval. Linkage analysis with the three highly informative microsatellite polymorphisms flanking FACC in 36 Fanconi anaemia families showed that only 8% of families were linked to this locus. This indicates that the genes for the other Fanconi anaemia complementation groups must map to one or more different chromosomal locations. The markers also allowed rapid exclusion of 56% of the families in our panel from complementation group C, thus substantially reducing the number of patients who need to be screened for FACC mutations.